Pengaruh Keterampilan Berpikir Krtis Terhadap Literasi Sains Siswa (UPEJ Unnes Physics Education Journal, 2019)
This study aims to describe the profile of critical thinking skills, the profile of scientific literacy, and determine the impact of critical thinking dexterity towards science literacy of junior high school student. The marking indicator of critical thinking includes argument analysis; deduction, considering deduction results; induction and considering induction result; identify terms and considering some terms. Science literacy ability includes 4 categories as follow: science as a cornerstone; science as thinking method; science as a way to investigate; also, science interaction, environment, technology and society. The method used in this study are correlational and data analysis technique using descriptive precentage and simple regression. Based on the result of simple regression analysis, critical thinking and science literacy have a significant and positive impact. The result of the analysis shows that students’ critical thinking dexterity is still lacking, their science literacy’s ability also lacking.